Probiotic Therapy Reduces Periodontal Tissue Destruction and Improves the Intestinal Morphology in Rats With Ligature-Induced Periodontitis - Messora, Michel R.; Oliveira, Luiz F. F.; Foureaux, Renata C.; Taba, Mario; Zangeronimo, Marcio G.; Furlaneto, Flavia A. C. [UNESP]; Pereira, Luciano J. (Amer Acad Periodontology, 2013)
Background: With increase in the incidence of resistance to antibiotics, probiotics are emerging as a promising adjunctive periodontal therapy. The authors of this study evaluate the influence of probiotic (PROB) supplementation on ligature-induced periodontitis (LIP) and intestinal morphology in rats.Methods: Thirty-two rats were randomly divided into four groups: control (C), LIP, PROB, and LIP/PROB. In groups PROB and LIP/PROB, the PROB was administered orally by addition to the drinking water of the animals for 44 days. In groups LIP and LIP/PROB, the mandibular right first molar of the animals received a cotton ligature that was left in the same position for 14 days. All animals were euthanized 44 days after the start of the PROB supplementation. The jaws were resected and histomorphometric analyses were performed. The measurements included evaluation of attachment loss (AL) and alveolar bone level (ABL) on the distal root of the mandibular first molar. Samples of the duodenum, jejunum, and ileum were also dissected from each animal to evaluate the villous height (VH) and crypt depth (CD). The data obtained were subjected to statistical analyses (analysis of variance, Tukey; P <0.05).Results: Mean values of AL and ABL were significantly higher in group LIP compared with group LIP/PROB (AL: 3.05 +/- 0.57 mm and 1.78 +/- 0.63 mm, respectively; ABL: 4.21 +/- 0.42 mm and 3.38 +/- 0.17 mm, respectively). In group LIP/PROB, the mean values of VH and CD of the jejunum were significantly higher than the ones from group LIP (VH: 672.1 +/- 83.3 mu m and 528.0 +/- 51.7 mu m, respectively; CD: 463.8 +/- 100.9 mu m and 269.0 +/- 48.4 mu m, respectively).Conclusions: It can be concluded that PROB supplementation 1) reduces AL and alveolar bone loss in rats with LIP and 2) can protect the small intestine from reactive changes induced by LIP.
Keywords: Alveolar bone loss; Bacillus subtilis; intestinal mucosa; periodontitis; probiotics; rats